Spinal versus General Anaesthesia for Laparoscopic Gynaecological Procedures: A Comparative Study of Haemodynamic Changes and Side Effects (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Laparoscopic gynaecological procedures are conventionally done under general anaesthesia. Spinal anaesthesia is usually preferred only in patients where general anaesthesia is contraindicated. For laparoscopic gynaecological procedures sub arachnoid block is gaining popularity day by day as it is a good alternative to GA.Objective: To compare haemodynamic changes and side effects between subarachnoid block (SAB) and general anaesthesia (GA) for lower abdominal laparoscopic gynaecological procedures.Materials and Methods: A total number of sixty female patients were considered and divided equally into two groups as per American Society of Anesthesiologists (ASA) grade I and II. All patients underwent short duration (